Blastocyst quality and perinatal outcomes of frozen-thawed single blastocyst transfer cycles - Jia, Nan; Hao, Haoying; Zhang, Cuilian; Xie, Juanke; Zhang, Shaodi (Frontiers in Endocrinology, 2022)
Objective To investigate the effects of blastocyst quality and morphological grade on the perinatal outcomes in patients undergoing frozen-thawed single blastocyst transfer cycles. Methods This single-center retrospective cohort study included 2648 singleton neonates resulting from frozen-thawed single blastocyst transfers performed between January 2017 and September 2021. Multivariate logistic regression was performed to evaluate perinatal outcomes for their association with blastocyst quality and morphological parameters. Result Transfer of a good-quality blastocyst in a frozen-thawed cycle was associated with a lower rate of preterm delivery (PTD, adjusted OR =0.7, 95% CI 0.5-0.9; P=0.020) and a higher likelihood of a male neonate (adjusted OR =1.2, 95%CI 1.0-1.5; P=0.048). Compared with grade C inner cell mass (ICM) blastocyst transfer, grade B ICM (adjusted OR =0.5, 95%CI 0.2-0.9; P=0.027) and grade A ICM (adjusted OR =0.6, 95%CI 0.3-1.5; P=0.290) blastocyst transfers were associated with a lower rate of PTD, which was more evident for grade B ICM. After adjusting for confounders, the likelihood of a male neonate (grade B TE, OR =1.2, 95%CI 1.0-1.5, P=0.037; grade A TE OR =1.9, 95%CI 1.3-28, P=0.002) increased with increasing trophectoderm (TE) quality. Compared with expansion stage 4, the likelihood of a male neonate was 1.5 times greater with transfer of a stage 6 blastocyst (OR =1.5, 95%CI 1.0-2.3; P=0.06), and the risk of small for gestational age (SGA) was greater with transfer of a stage 5 blastocyst (adjusted OR =3.5, 95%CI 1.5-8.0; P=0.004). The overall grading of the blastocyst, expansion stage, ICM grade, and TE grade were not associated with length at birth, birthweight, large for gestational age (LGA), or birth defects (all P>0.05). Conclusions In frozen-thawed single blastocyst transfer cycles, transfer of a good-quality blastocyst was associated with a lower rate of PTD and a greater likelihood of a male neonate. Transfer of grade B ICM blastocysts decreased the rate of PTD, and TE quality was positively correlated with the likelihood of a male neonate.